Chernikov 2-groups with the Kleinian top and totally reducible bottoms - Drozd, Yu. A.; Plakosh, А. І. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 512.54We give a classification of Chernikov 2-groups with Kleinian top and totally reducible bottom.